Pengembangan Media Pembelajaran Berbasis Figma Pada Mata Pelajaran Informatika Kelas VII SMP - Dwi Maulan Pangestu; Novrianti; Zuwirna; Meldi Ade Kurnia Yusri (Journal of Pedagogy and Online Learning, 2023)
This study aims to develop figma-based learning media in class VII informatics subjects and aims to test the feasibility of learning media products that have been used by seventh grade students of Angkasa Lanud Padang Junior High School with a total of 14 students conducted in July 2023. This type of research is R&D (Research and Development) development research using the 4-D model which consists of 4 stages namely Define, Design, Development and Disseminate. The results of validation from media experts obtained an overall average of 3.85 with a very valid category. While validation from material experts with an average score of 3.92 categories is very valid. The results of the practicality test on students get an average score of 3.7 with a very practical category. Based on these results, the figma-based learning media in informatics subjects in class VII SMP is valid and practical for use as a learning media in the classroom.